Про неоднозначне розуміння термінів “адаптація” і “акліматизація” в інтродукції рослин - Bulakh, P.E.; Elpitiforov, E.N.; Popil, N.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
The current state of the conceptual apparatus in plant introduction is considered. The necessity of an objective discussion of the existing diversity of views on the controversial concept of adaptation and acclimatization of plants is shown. The definitions of this terms are analyzed authors views on the process of adaptation of plants from the standpoint of reactions of norms and homeostasis of organisms are given. The biological significance of pre- and postadaptatsy is shown. Pre-adaptation we consider as an important factor in determining the adaptive capacity of plants. Adaptation is interpreted as a phenomenon, including naturalization and acclimatization of plants. In the first case there is a change in the range of genetically determined rate of reaction (modification variability), and in the second case – a change take place in the genotype, causing changes (genotypic variability) reaction norm. Thus, under the acclimatization we understand the process of adaptation of plants to a range of new environmental conditions in their resettlement or introduction associated with genotype change (reconstruction). We consider key and discussion questions of these concepts use in plant introduction.